Damage Features of Altered Rock Subjected to Drying-Wetting Cycles - Zhe Qin; Xuxin Chen; Houli Fu (Advances in Civil Engineering)
An abandoned open pit was used as a tailing pond for a concentrating mill, with the height of the water surface subject to cyclic fluctuation. The effects of drying and wetting cycles on the mechanical parameters of pit rock were tested. Interactions of the hydrochemical environment, due to the dissolution of tailings, and drying and wetting cycles caused degradation of mechanical properties in the rock. It was found that uniaxial compressive strength and elastic modulus decreased as the number of dry/wet cycles increased. The quantitative relationship between the mechanical parameters and the number of dry/wet cycles was indicated by an exponential function. In addition to uniaxial testing, cohesion and the internal friction angle were determined through triaxial testing. The shear strength index deteriorated under the drying and wetting cycles. The hydrochemical environment also negatively affected the mechanical parameters. Potential effects between drying and wetting cycles and slope displacement were analyzed by on-site monitoring. The results show that the displacement increased because of the drying and wetting cycles, which may lead to sudden failure of the slope.